2015
DOI: 10.1111/1753-0407.12325
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine‐disrupting chemicals, risk of type 2 diabetes, and diabetes‐related metabolic traits: A systematic review and meta‐analysis

Abstract: Persistent and non-persistent EDCs may affect the risk of T2D. There is an urgent need for further investigation of EDCs, especially non-persistent ones, and T2D risk in large prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(109 citation statements)
references
References 74 publications
(195 reference statements)
2
99
0
2
Order By: Relevance
“…Growing evidence suggests that presence of persistent organic pollutants (e.g., dioxins, polychlorinated biphenyls) may partly reduce cardiometabolic benefits of fish consumption; 213-215 less evidence suggests potential for net harm, due to the opposing benefits of omega-3's. Methylmercury consumed from fish has no detectable influence on incident cardiovascular events, hypertension, or diabetes.…”
Section: Foods and Cardiometabolic Healthmentioning
confidence: 99%
“…Growing evidence suggests that presence of persistent organic pollutants (e.g., dioxins, polychlorinated biphenyls) may partly reduce cardiometabolic benefits of fish consumption; 213-215 less evidence suggests potential for net harm, due to the opposing benefits of omega-3's. Methylmercury consumed from fish has no detectable influence on incident cardiovascular events, hypertension, or diabetes.…”
Section: Foods and Cardiometabolic Healthmentioning
confidence: 99%
“…These receptors play a critical role in normal biology and development [75], including energy balance and glucose homeostasis [76]. Though the exact mechanisms of action remain unknown, multiple studies support an association between endocrine disruptors and metabolic syndrome [77, 78], which may partially explain how chronic exposure to iAs has been associated with pathophysiological illnesses such as T2D.…”
Section: Arsenic and T2d Pathophysiologymentioning
confidence: 99%
“…In this last decade, a number of studies have investigated the association between BPA and T2DM, mostly on the basis of the results derived from data of the National Health and Nutrition Examination Survey (NHANES) [5,6,7,8,9,10,11,32,33]. Lang et al found a positive association between urinary BPA levels and prevalence of T2DM using cross-sectional data from NHANES 2003–2004 [6].…”
Section: Epidemiological Evidences: Observational Studies In Humansmentioning
confidence: 99%
“…Indeed, either genetic or environmental factors contribute to the risk of occurrence of T2DM [4]. In particular, among the environmental factors, mounting evidence suggests that the exposure to environmental endocrine disrupting chemicals (EDCs) might play a role in the pathogenesis of T2DM [5]. …”
Section: Introductionmentioning
confidence: 99%